Investigation of RNA Viruses in Culicoides Latreille, 1809 (Diptera: Ceratopogonidae) in a Mining Complex in the Southeastern Region of the Brazilian Amazon - Sâmia Luzia Sena da Silva; Sandro Patroca da Silva; Carine Fortes Aragão; Inocêncio de Sousa Gorayeb; Ana Cecília Ribeiro Cruz; Daniel Damous Dias; Bruna Laís Sena do Nascimento; Jannifer Oliveira Chiang; Lívia Medeiros Neves Casseb; Joaquim Pinto Nunes Neto; Lívia Carício Martins; Pedro Fernando da Costa Vasconcelos (Viruses)
The biting midges Culicoides Latreille, 1809 (Diptera: Ceratopogonidae) is highly relevant to epidemiology and public health, as it includes species that are potential vectors of human and animal arboviruses. The aim of this study was to investigate the presence of RNA viruses in species of the genus Culicoides collected in the Carajás mining complex in the state of Pará. The biting midges were collected in the municipalities of Canaã dos Carajás, Curionópolis and Marabá and morphologically identified. A total of 1139 specimens of seven Culicoides species were grouped into eight pools and subjected to metagenomic analysis. Eight new insect-specific viruses (ISVs) were characterized and assigned to the order Tolivirales, the families Chuviridae, Nodaviridae, Iflaviridae, Mesoniviridae, and Flaviviridae, and the taxon Negevirus. All viruses identified were assigned to clades, families and taxa never reported in Culicoides in Brazil. This study demonstrated that biting midges harbor a significant diversity of RNA viruses, many of which are still unknown, highlighting the importance of studies aiming at virome of these insects.